Impact of Chemical Waste Discharge on BOD Removal in Sewerage Treatment Plant - Nor Azman, Mohd Fadly (Universiti Teknologi Petronas, 2004)
The performance system of the aeration tank and clarifier was studied to enhance the performance ofUniversity Technology Petronas (UTP) sewage treatment plant (STP). A pilot plant with feeder tank, aeration tank and clarifier was used to simulate UTP's STP. The parameters evaluated in the study were biological oxygen demand (BOD), the concentration of dissolve oxygen (DO) and the performance of pilot plant after the addition of segregated chemical waste. To simulate the exact condition ofexisting UTP's STP, the flowrate was scaled down from 0.4 Ml/hour in the STP to only 41/hour in pilot plant, which is about 1:6 ratio. For the first five weeks, no return activated sludge from clarifier to aeration tank to simulate the problem in the STP. For the last five weeks, the activated sludge pilot plant was operated in normal condition. Chemical waste (approximately 20% concentration from total influent) from chemical blocks was also added in stages into the feeder tank along withthe normal wastewater. The highest BOD influent value for STP and pilot plant were 92 mg/1 and 30 mg/1, respectively. The highest BOD effluent value for STP and pilot plant"were 22 mg/I and 11 mg/1, respectively. The addition of20% segregated chemical waste from chemical blocks did not have any significant effects to the performance of pilot plant.